PSYCHOLOGICAL ANALYSIS OF PARENT-CHILD RELATIONSHIPS IN PRIMARY SCHOOL STUDENTS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article examines the psychological aspects of parent-child relationships in primary school students, focusing on how family dynamics, emotional bonds, and communication patterns influence the child’s development. The parent-child relationship at this age is particularly important, as it forms the basis for children’s self-esteem, social adaptation, and academic success. Drawing on developmental psychology and family systems theory, the study explores how parental warmth, support, and discipline contribute to emotional security and personality growth, while conflict, neglect, or inconsistency may result in behavioral or psychological difficulties. The analysis also considers the role of cultural traditions and educational expectations in shaping the nature of family interactions. Special attention is given to the ways in which parenting styles—authoritative, authoritarian, permissive, and neglectful—impact children’s adjustment to school, peer relationships, and self-concept. The article further highlights the importance of effective communication and mutual trust between parents and children, as these are central to fostering resilience, responsibility, and positive emotional development. By identifying both challenges and opportunities within the parent-child relationship, the study emphasizes the need for supportive strategies that promote healthy family environments. The findings suggest that the psychological well-being of primary school students is closely tied to the quality of their relationships with parents, making this an essential area of focus for educators, psychologists, and policymakers interested in child development and pedagogy.